Design and Development of Solar Pump System for Automatic Watering of Shallots - Muh. Ilham; Yuliana; Idris, Ahmad Rosyid; Usman; Achmad, Alamsyah (Jurnal Teknologi Elekterika, 2024)
Agriculture is a key sector of the Indonesian economy, with shallots being one of the most important commodities. However, limited access to electricity in rural areas is often a barrier to the implementation of efficient irrigation systems. This research focuses on developing an automatic shallot irrigation system using a solar pump. The system is designed by using solar panels to convert solar energy into electricity to power the water pump. They use an Arduino-based control system integrated with a real-time clock (RTC) to automatically set the watering schedule so that plants can be watered at the right time without human intervention. Tests were conducted on 96 m² of land to evaluate the performance of the automation system, energy efficiency, and system performance under actual operating conditions. The testing results show that the system can operate efficiently, with the solar panel generating enough energy to power the pump and maintain watering continuity. The system can reduce dependence on conventional electricity, providing a sustainable and environmentally friendly irrigation solution. As such, the system provides an effective solution for agricultural systems in areas with limited access to electricity, while supporting the use of renewable energy.